UJI KUALITAS MOL AIR BUAH SIWALAN (Borassus flabellifer) DENGAN PENAMBAHAN BERBAGAI JENIS BUAH BERDASARKAN LAMA FERMENTASI - Irpan, Irpan; Caronge, Muhammad Wiharto; Fadilah, Ratnawaty (Jurnal Pendidikan Teknologi Pertanian, 2018)
The purpose of this study was to determine the quality of local microorganisms (MOL) produced from various types of fruit. This research method uses a completely randomized (ral) factorial pattern design with 2 factors, the first factor is the addition of papaya and banana. While the second factor is the length of fermentation time is 0 days and 7 days. The data was processed using of ANOVA analysis techniques with further test duncan. The results showed that local microorganisms with the addition of papaya fruit were the best treatment with value that were 1.49% nitrogen levels, 0.12% phosphorus levels, 0.71% potassium levels, and total microbes from day 0 to 5.79 log10 colony/ml, and 7th day that is 7.87 log10 colony/ml.